Genetics of Hypercholesterolemia: Comparison Between Familial Hypercholesterolemia and Hypercholesterolemia Nonrelated to LDL Receptor - Jarauta, Estíbaliz; Bea-Sanz, Ana Ma; Marco-Benedi, Victoria; Lamiquiz-Moneo, Itziar (Frontiers in Genetics, 2020)
Severe hypercholesterolemia (HC) is defined as an elevation of total cholesterol (TC), due to the increase of LDL cholesterol (LDL-C) > 95th percentile or 190 mg/dL. The high values of LDL-C, especially when it is maintained over time, it is considered a risk factor for the development of atherosclerotic cardiovascular disease (ASCVD), mostly expressed as ischemic heart disease (IHD). One of the best characterized forms of severe HC, Familial Hypercholesterolemia (FH) is caused by the presence of a major variant in one gene (LDLR, APOB, PCSK9 or ApoE), with an autosomal co-dominant pattern of inheritance, causing an extreme elevation of LDL-C and early ischemic heart disease (IHD). Nevertheless, an important proportion of serious HC cases, denominated Polygenic Hypercholesterolemia (PH), may be attributed to the small additive effect of a number of single nucleotide variants (SNV), located along the whole genome. The diagnosis, prevalence and cardiovascular risk associated with PH has not been fully established at the moment. Cascade screening to detect a specific genetic defect is advised in all first- and second-degree relatives of subjects with FH. Conversely, in the rest of cases of HC, it is only adviced the screening of high values of LDL-C in first degree relatives, since there is not a consensus for the genetic diagnosis of PH. FH is associated with the highest cardiovascular risk, followed by PH and other forms of HC. Early detection and initiation of high-intensity lipid lowering treatment is proposed in all subjects with severe HC for primary prevention of ASCVD, with an objective of LDL-C <100 mg/dl or a decrease of at least 50%. A more aggressive reduction of LDL-C is necessary in HC subjects who associate personal history of ASCVD or other cardiovascular risk factors